Pelatihan Public Speaking untuk Melatih Keterampilan Berbicara bagi Siswa SMPN 8 Tambang Kabupaten Kampar - Febria, Rhani; Alber, Alber; Alpen, Joni; Asnawi, Asnawi; Putri, Nadila; Ardila, Della (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
The development of science and technology demands good public speaking skills for everyone, including junior high school students. However, many students face obstacles such as nervousness, anxiety, and a lack of self-confidence when speaking in public. This community service activity aimed to provide public speaking training to improve students' speaking skills at SMPN 8 Tambang. The activity was held on December 14, 2024, involving 30 participants, through the delivery of material on basic concepts, vocal, visual, and verbal techniques, as well as public speaking practice sessions. The results showed that prior to the training, only 16.67% of students dared to speak in public. After the training, there was a significant increase in students' confidence and ability to speak effectively. Students were also able to apply good public speaking techniques, including vocal control, posture, and mastery of material. This training received enthusiastic responses and is recommended to be continued through extracurricular activities to sustainably enhance students' public speaking skills.